Urraca I e a governança feminina: uma análise das representações sociais na Península Ibérica Medieval - Alves, Janaina Dos Reis (2017)
This dissertation intend to analyze the social representations of Urraca I, queen of Leon and Castile during the first half of the twelfth century, from the chronicle Historia Compostelana and other contemporary documents such as the Chronicles of Sahagún and the administrative diplomats written during her governance. Faced the multiple representations produced of Urraca I, sometimes valued for her government performance, sometimes underestimated by her feminine condition, we identified that her representation is directly related with production context of the works about her. Thus we propose a journey through the historiography, in the invested of understanding the feminine paper of this ruler in the Leonese court of the twelfth century, through the theory of the social representation explained by Serge Moscovici. Our main challenge is to unite these multiple representations into an object of learning that serves to guide the continuing education of professionals dedicated to teaching history in basic education. In this case, we chose to develop a course on the Moodle platform that works on the analysis and production of historical narratives about the Iberian woman in the Middle Ages, willing to unite source and historiographical reflection in the teaching of history in basic education.